Directing and producing for television : a format approach - Cury, Ivan. (New York : Elsevier, 2011)
Directing and producing for television with a multi-camera approach takes skill, innovation, and precise planning. This book gives you the tools you need to effectively direct and produce television. The conversational style of the book includes instructional anecdotes scattered throughout each chapter, showing you how to avoid common pitfalls in directing for television and how to create excellent programs. --
Directing and Producing for Television addresses critical production techniques for various formats, including panel discussions, demonstrations, music, commercials, PSAs, news, documentaries, reality television, remote broadcasts, and sports. Written with both the director and producer in mind, but particularly relevant for the television director, Directing and Producing for Television gives a comprehensive overview of the facility (studio, control room, and support areas) and details the various jobs and personnel involved in television programs. --
In-depth coverage of script formats, schedules, and routines, along with a core focus on fundamental principles behind directing for television, make this a complete guide for beginning television directors. --Book Jacket.
Facility -- Who's Who -- Panel Programs -- Demonstration Format -- Scripted Format -- Music -- Commercials and Public Service Annoucements -- News -- Documentaries and Reality Programming -- Multiple-Camera Remotes.
Includes bibliographical references and index.
Keywords: Television -- Production and direction